A systematic study of the phosphate-bearing sedimentary rocks of Tehri Garhwal, Uttarakhand: constraining the paleo-redox conditions - Vikash Kumar; Shamim A. Dar; Nozmul Karim; Mohammad Javed; Sumit K. Ghosh (Carbonates and Evaporites, 2026)

Warming responses, antibiosis potentials, and ecological implications of cryo-adapted copiotrophs from a Trans-Himalayan lake-desert ecosystem - Sumit Chatterjee; Subhajit Dutta; Jit Ghosh; Swapneel Saha; Mahamadul Mondal; Jagannath Sarkar; Nibendu Mondal; Wriddhiman Ghosh (Archives of Microbiology, 2026)

Analysis of microsatellites (SSRs) of Curvularia geniculata strain SKG23 isolated from leaf spot disease of Mentha (Mentha arvensis L.) - Sumit Kumar Polley; Swapan Kumar Ghosh (Vegetos, 2026)

Decoding the Impact of Acidification and Toxic Metal Stress on Tea Soil Bacteriome: Integrating 16S rRNA Sequencing with Multivariate Approaches - Riddhi Basu; Sonali Banerjee; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Pradip Bhattacharyya (Biological Trace Element Research, 2026)

Lung Cancer in Non-Smokers: Molecular, Immunological and Potential Therapeutic Approaches - Debanik Deb; Sumit Ghosh; Shauryabrota Dalui; Avijit Dey; Parames C. Sil (Indian Journal of Clinical Biochemistry, 2026)

Assessing the geochemical impacts of bauxite mining to the neighbouring environment: a quantitative approach through risk assessment, sensitivity analysis and source apportionment of heavy metals - Mohammad; Gourav Mondal; Saibal Ghosh; Sumit Kumar; Pradip Bhattacharyya (Environmental Geochemistry and Health, 2026)

Harnessing the anti and pro-oxidants potential of selenium - Dibyajyoti Nath; Sayali Biradar; Sumit Sow; Shiva Nath Suman; Vipin Kumar; Shivani Ranjan; Santosh Kumar Singh; Hemlata Singh; Ranjan Laik; Mainak Ghosh; Lalita Rana (Journal of Trace Elements in Medicine and Biology, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Intensification of rice-wheat cropping system with summer green gram improves growth, productivity and profitability of rice in the middle Indo-Gangetic Plains of India - Manish Raj; Sushant; Mainak Ghosh; Anil Kumar Singh; Sumit Sow; Sanjay Kumar; Birendra Kumar; Swaraj Kumar Dutta; Nintu Mandal; Pritam Ganguly; Arnab Roy Chowdhury; Shishpal Poonia; et al. (European Journal of Agronomy, 2026)

A Critical Review of Agribots and Intelligent Systems for Sugar Crop Health and Farmer Advisory - Sudipta Mahato; Ritwik Sahoo; Dipankar Barai; Waghamare Minal Bhujangrao; Sumit Sow; Shivani Ranjan; Subir Dutta; Dibyendu Ghosh (Sugar Tech, 2026)

Deciphering stone mining-induced hazardous heavy metal contamination in agricultural soils using source attribution, health-dietary risk analysis, and machine learning-driven insights - Annewsa Acharya; Chetana Tunga; Sonali Banerjee; Riddhi Basu; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Shreya Chakraborty; Gopinath Gorai; Sudipta Tripathi; Pradip Bhattacharyya (Environmental Geochemistry and Health, 2026)

Tracing environmentally hazardous metal pollution in iron mine-influenced agro-ecological regions: Insights from soil quality indices, source attribution, and health-risk appraisal - Debatri Dewanjee; Sumit Kumar; Sonali Banerjee; Gourav Mondal; Saibal Ghosh; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2026)

Chamomile Modulates Glucose Metabolism and Neuro-inflammation to Alleviate Stress-Induced Depression in Mice - Shauryabrota Dalui; Sreejit Pal; Anamitra Goswami; Aritya Sinha; Suman Karar; Arpan Saha; Preetam Modak; Moumita Sil; Prashant Ratnaparkhi; Arunava Goswami; Sumit Ghosh; Abhishek Choudhury; et al. (Molecular Neurobiology, 2026)

Geochemistry and U–Pb Geochronology of Volcaniclastic Rocks From the NW Lesser Himalayan Sequence: Implications for Arc‐Related Tectonic Setting at Northern Proto‐Indian Continental Margin During the Neoproterozoic - Subhojit Saha; Kaushik Das; Shivani S. Choudhari; Abhishek Kumar Pandey; Shruti Ranjan Mishra; Sumit Kumar Ghosh; Alok Deep; Partha Pratim Chakraborty (Island Arc, 2026)
The protracted tectonic history concerning the northern edge of the pre‐Himalayan proto‐Indian plate margin during the Neoproterozoic time has been a long‐standing subject of debate, with various hypotheses enduring over several decades. Although a continental rift to passive margin setting has been proposed for the deposition of Neoproterozoic rocks of the Outer Lesser Himalayan Sequence (OLHS), the similarity in detrital zircon age peaks and Nd isotope values of OLHS rocks with those of the Higher Himalayan Crystalline Sequence (HHCS) led to the proposition of an arc‐related setting. So far, there is no such report of Neoproterozoic arc‐related magmatism from the Lesser Himalayan Sequence. In the present study, an interbedded volcaniclastic horizon has been identified from the basal stratigraphic level of the Nagthat Formation, OLHS. Geochemistry and U–Pb zircon geochronology are used to understand the provenance and tectonic setting of the Nagthat volcaniclastic rock. The angularity of the framework minerals, moderate degree of weathering (avg. Chemical Index of Alteration value 62), and immature nature (Index of Compositional Variability 1–1.1) suggest that a contemporaneous volcanic province was probably the main source. Whole rock geochemical analysis shows high Th/Sc (1.67–3.40, avg. 2.71), La/Sc (4.74–8.21, avg. 7.14), and low Cr/Th ratios (1.78–5.45, avg. 3.02). It supports that the volcaniclastic was supplied from an acid to intermediate source rocks, such as rhyolite and dacite/andesite. U–Pb detrital zircon analysis yielded a major age peak around 775 Ma. However, comparison of the U–Pb zircon age data with published datasets from the Lower (Chandpur Formation) and upper (Nagthat Formation) stratigraphic horizons suggests a timing of volcanism between 800 and 700 Ma. Geochronological and geochemical characteristics of the volcaniclastic rock suggest a signature transitional from passive to active continental margin setting, indicating that at least subduction was ongoing during the Tonian (800–700 Ma) at the northern proto‐Indian plate margin.

Unveiling the synergistic impact of heavy-metals and alkalinity on microbial diversity using machine learning techniques - Gourav Mondal; Sonali Banerjee; Saibal Ghosh; Sumit Kumar; Pradip Bhattacharyya (Environmental Sustainability, 2025)

Microbial–viral synergy in Eisenia fetida gut supports earthworm survival, detoxification, and functional resilience - Partha Barman; Anukul Paul; Shilpa Sinha; Tilak Saha; Nibendu Mondal; Subhajit Dutta; Sumit Chatterjee; Wriddhiman Ghosh; Ranadhir Chakraborty (Science of The Total Environment, 2025)

Harnessing vermicomposted chromite-asbestos mine waste for sustainable chilli production: a focus on biochemical traits and yield enhancement with machine learning insights - Sonali Banerjee; Sonam Jha; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Pradip Bhattacharyya (Clean Technologies and Environmental Policy, 2025)

Aldose reductase inhibitor for delaying galactose-induced cataract formation in wistar rats by isolated and characterized natural products from Cuscuta reflexa - Saroj Singhmura; Tanmoy Banerjee; Sumit Dutta; Poulomi Mishra; Souvik Basak; Nilanjan Ghosh (Natural Product Research, 2025)

Whole genome sequencing, assembly and annotation of Curvularia geniculata strain SKG23 isolated from leaf spot disease of mentha (Mentha arvensis L.) - Swapan Kumar Ghosh; Sumit Kumar Polley (Vegetos, 2025)

Source apportionment and risk assessment of heavy metals in mangrove soils using multivariate and sensitivity analyses - Annewsa Acharya; Debatri Dewanjee; Gourav Mondal; Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Riddhi Basu; Sumit Roy; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2025)

Biofortified vermicompost: Exploring bacterial community dynamics and enzymatic pathways through bacteriome analysis for arsenic bioremediation in mine waste - Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Pritam Mukherjee; Souvik Das; Pradip Bhattacharyya (Environmental Pollution, 2025)

Taurine alleviates colitis by regulating oxidative stress, inflammatory responses, ER stress, and apoptotic pathways - Ankita Mandal; Sharmistha Banerjee; Sumit Ghosh; Parames C. Sil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comprehensive Evaluation of Potentially Toxic Elements in Tea: Bioavailability, Bio-accessibility, and Health Risk Analysis Using Multimodal Statistics - Riddhi Basu; Saibal Ghosh; Gourav Mondal; Sonali Banerjee; Shreya Chakraborty; Sumit Kumar; Pradip Bhattacharyya (Biological Trace Element Research, 2025)

Enhancing mycophytoremediation potential of Chrysopogon zizanioides in chromite-asbestos mine waste soil using arbuscular mycorrhizal fungi: A natural bioaccelerator for soil ecosystem rehabilitation - Sonali Banerjee; Saibal Ghosh; Sonam Jha; Sumit Kumar; Dibyendu Sarkar; Rupali Datta; Pradip Bhattacharyya (Science of The Total Environment, 2025)

Paleo-productivity reconstruction in Bay of Bengal during the past 1.3 Ma: Implications for glacial-interglacial dynamics and southern hemispheric processes - Barnita Banerjee; Monalisa Mallick; Vikash Kumar; E.V.S.S.K. Babu; Ozelim Luan; G. Balu; T. Vijaya Kumar; Nihar Ranjan Kar; Tanveer Hassan; Manish Tiwari; Thamizharasan Sakthivel; Prosenjit Ghosh; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Development of new spectral indices for mapping of crop residue burning using satellite remote sensing - Sumit Kumar; Sanjay Kumar Ghosh; Brijendra Pateriya (International Journal of Remote Sensing, 2025)

A Multifaceted Approach Assessing Heavy Metal Contamination and Health Risk in Tea Garden Soils: Insight Through Hot-Spot Analysis and Machine Learning Techniques - Riddhi Basu; Sonali Banerjee; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Jajati Mandal; Pradip Bhattacharyya (Water, Air, & Soil Pollution, 2025)

Determination of beneficial effects of cuminaldehyde on hyperglycemia associated kidney malfunctions - Abhishek Kumar Das; Sumit Ghosh; Parames C. Sil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genome editing: A novel approach to manage insect vectors of plant viruses - Sumit Jangra; Jesse Potts; Amalendu Ghosh; Dakshina R. Seal (Insect Biochemistry and Molecular Biology, 2024)

Dynamics and fisher perception of fishery exploitation in a transboundary pocket of the River Atrai, India - Monika Ghosh; Soumyadip Panja; Mrinmay Dutta; Sumit Homechaudhuri (Fisheries Management and Ecology, 2024)
Transboundary freshwater fish are critical for both biodiversity and community well‐being but face alarming overexploitation in shared rivers. Such rivers greatly aid the livelihood and nutrition of local people on both sides of shared borders. However, a lack of understanding of resource dynamics and utilization patterns hinders sustainable management of resources. We investigated spatiotemporal fish assemblages along the River Atrai, a transboundary river between India and Bangladesh. The socioeconomic status of fishers was quantified from personal interviews and group discussions to estimate the exploitation trajectory of piscine resources. Fish assemblages varied significantly among locations and seasons. Species diversity was highest downstream and lowest upstream. Spatiotemporal fishery exploitation aligned with fish diversity among sites and seasons, with fishers preferring to fish in downstream areas during the post‐monsoon season. Fishers were economically weak, with limited sources of income. Therefore, adequate integrated management plans should be implemented to ensure resource resilience in a transboundary pocket, sustainably supporting the livelihood of concomitant fishers.

Earthquake-induced deformation structures along Trans-Yamuna active fault system: Doon Valley, NW Himalaya - Rekha; Sumit K Ghosh (Journal of Earth System Science, 2024)

Customized Extrusion Nozzle Assisted Robust Nylon 6/MWCNT Nanocomposite Based Triboelectric Nanogenerators for Advanced Smart Wearables - Sunanda Roy; Barnali Dasgupta Ghosh; Sumit Mishra; Kheng Lim Goh; Jaehwan Kim (Chemical Engineering Journal, 2024)

The Emerging Role of Natural Products in Cancer Treatment - Sumit Ghosh; Sanjib Kumar Das; Krishnendu Sinha; Biswatosh Ghosh; Koushik Sen; Nabanita Ghosh; Parames C. Sil (Archives of Toxicology, 2024)

Microbial diversity associated with the natural spring water of Western Himalayas - Yukti Oza; Mrunal Karande; Rochita Ghosh; Janhvi Mishra Rawat; Sumit Purohit; Balwant Rawat; Alimuddin Zumla; Avinash Sharma (Vegetos, 2024)

U–Pb zircon geochronology of the Proterozoic siliciclastic stratal succession of the Kumaun Lesser Himalaya: Implications for regional stratigraphic correlation - Poonam Jalal; Sumit K Ghosh; Mohit Puniya; Gajender Kumar (Journal of Earth System Science, 2024)

Revealing soil microbial ecophysiological indicators in acidic environments laden with heavy metals via predictive modeling: Understanding the impacts of black diamond excavation - Sumit Kumar; Shreya Chakraborty; Saibal Ghosh; Sonali Banerjee; Gourav Mondal; Pankaj Kumar Roy; Pradip Bhattacharyya (Science of The Total Environment, 2024)

ApCPS2 contributes to medicinal diterpenoid biosynthesis and defense against insect herbivore in Andrographis paniculata - Anchal Garg; Payal Srivastava; Praveen Chandra Verma; Sumit Ghosh (Plant Science, 2024)

Metabolomic and genomic insights into TMA degradation by a novel halotolerant strain - Paracoccus sp. PS1 - Madhupa Seth; Priyajit Mondal; Dhritishree Ghosh; Raju Biswas; Sumit Chatterjee; Subhra Kanti Mukhopadhyay (Archives of Microbiology, 2024)

Extremely oligotrophic and complex-carbon-degrading microaerobic bacteria from Arabian Sea oxygen minimum zone sediments - Jagannath Sarkar; Mahamadul Mondal; Sabyasachi Bhattacharya; Subhajit Dutta; Sumit Chatterjee; Nibendu Mondal; Saran N; Aditya Peketi; Aninda Mazumdar; Wriddhiman Ghosh (Archives of Microbiology, 2024)

Elucidating the synergistic effect of acidity and metalloid poisoning on the microbiome through metagenomics and machine learning approaches - Shreya Chakraborty; Saibal Ghosh; Sonali Banerjee; Sumit Kumar; Pradip Bhattacharyya (Environmental Research, 2024)

Tungsten-based Lindqvist and Keggin type polyoxometalates as efficient photocatalysts for degradation of toxic chemical dyes - Gajiram Murmu; Soumita Samajdar; Srabanti Ghosh; K. Shakeela; Sumit Saha (Chemosphere, 2024)

Unraveling the terpene synthase family and characterization of BsTPS2 contributing to (S)-( +)-linalool biosynthesis in Boswellia - Pravesh Bhargav; Seema Chaurasia; Aashish Kumar; Gaurav Srivastava; Yatish Pant; Chandan Singh Chanotiya; Sumit Ghosh (Plant Molecular Biology, 2023)

Assessing pollution and health risks from chromite mine tailings contaminated soils in India by employing synergistic statistical approaches - Sonali Banerjee; Saibal Ghosh; Sonam Jha; Sumit Kumar; Gourav Mondal; Dibyendu Sarkar; Rupali Datta; Abhishek Mukherjee; Pradip Bhattacharyya (Science of The Total Environment, 2023)

Itraconazole Confers Cytoprotection Against Neurodegenerative Disease-Associated Abnormal Protein Aggregation - Ankur Rakesh Dubey; Ribhav Mishra; Yuvraj Anandrao Jagtap; Sumit Kinger; Prashant Kumar; Rohan Dhiman; Somnath Ghosh; Sarika Singh; Amit Prasad; Nihar Ranjan Jana; Amit Mishra (Molecular Neurobiology, 2023)

Enantioselective terpene emission signifies forest climate response mechanism - Sumit Ghosh (Trends in Plant Science, 2023)

Landfill leachate valorization: A potential alternative to burden off resources and support energy systems - Smita S. Kumar; Amit Kumar; Sandeep K. Malyan; Pooja Ghosh; Madan Kumar; Rimika Kapoor; Ajay Kumar Agrawal; Sumit Kumar; Vivek Kumar; Lakhveer Singh (Fuel, 2023)

Diabetes: discovery of insulin, genetic, epigenetic and viral infection mediated regulation - Sumit Ghosh; Sushweta Mahalanobish; Parames C. Sil (The Nucleus, 2022)

Application of virus-induced gene silencing in Andrographis paniculata, an economically important medicinal plant - Anchal Garg; Shubha Sharma; Payal Srivastava; Sumit Ghosh (Protoplasma, 2021)

Host plant influences life cycle, reproduction, feeding, and vector competence of Thrips palmi (Thysanoptera: Thripidae), a vector of tospoviruses - Heena Dhall; Sumit Jangra; Y. B. Basavaraj; Amalendu Ghosh (Phytoparasitica, 2021)

Disentangling the Effect of Seasonal Dynamics on Meiobenthic Community Structure From River Matla of Sundarbans Estuarine System, India - Moumita Ghosh; Sumit Mandal (Frontiers in Marine Science, 2021)
In estuarine sediment, meiobenthos serve as an excellent candidate to perform a range of ecosystem services. However, even though the taxonomic sufficiency of meiobenthos in detecting spatiotemporal gradients is well recognized, very little is known about their functional attributes in response to environmental descriptors. To bridge this knowledge gap, the taxonomic structure and trait-based functional diversity patterns of meiobenthic assemblage, focusing on nematode species composition, were assessed for the first time from the unexplored central sector of Sundarbans Estuarine System (SES). Sediment samples were collected seasonally (monsoon, winter, spring, and summer) selecting a total of eight stations across River Matla (the widest and longest river of SES). Distinct seasonal successional patterns had been observed in meiobenthic abundance modulated by seasonal alteration in the sedimentary environment (PERMANOVA, p < 0.05). Our study revealed a strong preponderance of meiobenthic density in spring (2978 ± 689.98 ind. 10 cm –2 ) and lowest during monsoon (405 ± 51.22 ind. 10 cm –2 ). A total of 11 meiobenthic taxa were identified with the dominance of nematodes. Altogether, 79 species of nematode belonging to 22 families had been identified across the entire study area and nematode assemblage was dominated by Sabatieria praedatrix , Sphaerolaimus balticus , Desmodora communis , Dorylaimopsis punctata , and Daptonema hirsutum . Principal component analysis depicted a distinct separation of seasons with reference to environmental variables. Distance-based redundancy analysis delineated that meiobenthic communities were mainly structured by organic matter, salinity, and dissolved oxygen concentration. Biological trait analyses of nematode assemblages were applied to gather the ecological information based on morphological and ecological characteristics. The most common morphotypes were slender body shape, clavate tail shape, striated cuticle pattern, and non-selective deposit feeders with colonizing abilities of 2–3 (c–p score in a scale from 1 to 5). Results from BIO-ENV showed that sediment organic matter and dissolved oxygen played overriding roles in shaping the functional compositions of nematodes. Thus, the characterization of meiobenthos and nematode assemblages in the context of taxonomic as well as functional attributes represents a first step toward building of baseline data which could help to evaluate the ecological status of SES and direct future research priorities concurrently.

A rapid field-based assay using recombinase polymerase amplification for identification of Thrips palmi, a vector of tospoviruses - Priti; Sumit Jangra; V. K. Baranwal; Ralf G. Dietzgen; Amalendu Ghosh (Journal of Pest Science, 2021)

ROS-associated immune response and metabolism: a mechanistic approach with implication of various diseases - Sharmistha Banerjee; Sumit Ghosh; Ankita Mandal; Noyel Ghosh; Parames C. Sil (Archives of Toxicology, 2020)

Exposure to watermelon bud necrosis virus and groundnut bud necrosis virus alters the life history traits of their vector, Thrips palmi (Thysanoptera: Thripidae) - Amalendu Ghosh; Y. B. Basavaraj; Sumit Jangra; Amrita Das (Archives of Virology, 2019)

Living with Nematode: an Epibiont Trematosoma rotunda Associated with Basibiont Desmodora scaldensis from Matla Estuary, Sundarbans, India - Moumita Ghosh; Sumit Mandal (Thalassas: An International Journal of Marine Sciences, 2019)

A Novel Method for Permeability Estimation from Micro-tomographic Images - Soumyadeep Paul; Sumit Roy; Pradyumna Ghosh; Mohammad Amin Faghihi Zarandi; Thomas Cender; Krishna M. Pillai (Transport in Porous Media, 2019)

Short-term variations in surface water properties in the Sundarban Estuarine System, India - Tanmoy Nandy; Sumit Mandal; Soumya Deb; Moumita Ghosh; Tirthankar Nath; Meenakshi Chatterjee (Sustainable Water Resources Management, 2018)

Anti-cancer labdane diterpenoids from adventitious roots of Andrographis paniculata: augmentation of production prospect endowed with pathway gene expression - Sailendra Singh; Pallavi Pandey; Sumit Ghosh; Suchitra Banerjee (Protoplasma, 2018)

Free-living marine nematode diversity from the Indian coasts - Moumita Ghosh; Sumit Mandal (Marine Biodiversity, 2018)

Exploring groundwater potential zones using MIF technique in semi-arid region: a case study of Hingoli district, Maharashtra - Sumit Das; Amitesh Gupta; Sasanka Ghosh (Spatial Information Research, 2017)

Characterization of a bacterioferritin comigratory protein family 1-Cys peroxiredoxin from Candidatus Liberibacter asiaticus - Anamika Singh; Narender Kumar; Prabhat P. S. Tomar; Sumit Bhose; Dilip Kumar Ghosh; Partha Roy; Ashwani K. Sharma (Protoplasma, 2017)

Depositional environment and tectono-provenance of Upper Kaimur Group sandstones, Son Valley, Central India - M. A. Quasim; A. H. M. Ahmad; Sumit K. Ghosh (Arabian Journal of Geosciences, 2017)

Magnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)

Loop-mediated isothermal amplification (LAMP) based method for rapid and sensitive detection of ‘Candidatus Liberibacter asiaticus’ in citrus and the psyllid vector, Diaphorina citri Kuwayama - Dilip Kumar Ghosh; Sumit Bhose; Ashish Warghane; Manali Motghare; Ashwani Kumar Sharma; Arun Kumar Dhar; Siddarame Gowda (Journal of Plant Biochemistry and Biotechnology, 2016)

Fruit ripening mutants reveal cell metabolism and redox state during ripening - Vinay Kumar; Mohammad Irfan; Sumit Ghosh; Niranjan Chakraborty; Subhra Chakraborty; Asis Datta (Protoplasma, 2016)

M agnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)
Summary Pathogens encounter and metabolize a range of host‐derived metabolites while proliferating inside the host. Our understanding of these metabolites and their metabolic processes has remained largely incomplete. We investigated the role of the M agnaporthe oryzae N ‐acetylglucosamine ( GlcNAc ) catabolic pathway during rice infection. The catabolic pathway is composed of a GlcNAc transporter ( MoNgt1 ), hexokinase(s), a GlcNAc ‐6‐phosphate deacetylase ( MoDac ) and a GlcN ‐6‐phosphate deaminase ( MoDeam ). A detailed characterization of the Δ mongt1 , Δ modac and Δ modeam null mutants revealed that a defect in GlcNAc catabolism impairs the pathogenicity of M . oryzae . These mutants showed severely reduced virulence in susceptible rice cultivar due to their inability to neutralize host‐derived reactive oxygen species and their failure to develop invasive hyphal growth within the host tissue. Interestingly, during oxidative stress, M . oryzae proliferated efficiently in GlcNAc ‐containing media compared with other sugars, and the expression of fungal antioxidant genes was upregulated following GlcNAc treatment. However, GlcNAc inhibited the growth of the Δ modac and Δ modeam mutants, and this growth inhibition was enhanced during oxidative stress. These results suggest that GlcNAc helps fungus to overcome oxidative stress inside its host, perhaps by activating an antioxidant defence. In the absence of a functional catabolic pathway, GlcNAc becomes toxic to the cells.

Potentiality of Bacterial Pathogens Including Invasive Exotic Species as Threat to Indigenous Fish Species - Sriparna Datta Ray; Rajarshi Ghosh; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2015)

Molecular characterization of Citrus yellow mosaic badnavirus (CMBV) isolates revealed the presence of two distinct strains infecting citrus in India - Dilip K. Ghosh; Sumit Bhose; Krishanu Mukherjee; Balaji Aglave; A. J. Warghane; Manali Motghare; V. K. Baranwal; Arun K. Dhar (Phytoparasitica, 2014)

Improved sanguinarine production via biotic and abiotic elicitations and precursor feeding in cell suspensions of latex-less variety of Papaver somniferum with their gene expression studies and upscaling in bioreactor - Priyanka Verma; Shamshad Ahmad Khan; Ajay K. Mathur; Sumit Ghosh; Karuna Shanker; Alok Kalra (Protoplasma, 2014)

Hyaluronan deposition and co-localization with inflammatory cells and collagen in a murine model of fungal allergic asthma - Sumit Ghosh; Amali E. Samarasinghe; Scott A. Hoselton; Glenn P. Dorsam; Jane M. Schuh (Inflammation Research, 2014)

Sequence and evolutionary analysis of ribosomal DNA from Huanglongbing (HLB) isolates of Western India - Dilip Ghosh; Sumit Bhose; Krishanu Mukherjee; V. K. Baranwal (Phytoparasitica, 2013)

Molecular detection of Candidatus Phytoplasma spp. causing witches’ broom disease of acid lime (Citrus aurantifolia) in India - Dilip Ghosh; Sumit Bhose; R. Manimekalai; S. Gowda (Journal of Plant Biochemistry and Biotechnology, 2013)

Provenance of the Late Neogene Siwalik sandstone, Kumaun Himalayan Foreland Basin: Constraints from the metamorphic rank and index of detrital rock fragments - POONAM JALAL; SUMIT K GHOSH (Journal of Earth System Science, 2012)

Polymorphisms of CYP1A1, GSTM1 and GSTT1 Loci as the Genetic Predispositions of Oral Cancers and Other Oral Pathologies: Tobacco and Alcohol as Risk Modifiers - Sumana Chatterjee; Soujatya Dhar; Bani Sengupta; Ashish Ghosh; Manas De; Sumit Roy; Sila Chakrabarti (Indian Journal of Clinical Biochemistry, 2010)

Seasonal variation in the biochemical composition of red seaweed (Catenella repens) from Gangetic delta, northeast coast of India - Kakoli Banerjee; Rajrupa Ghosh; Sumit Homechaudhuri; Abhijit Mitra (Journal of Earth System Science, 2009)